2019
DOI: 10.1038/s41467-018-07932-1
|View full text |Cite
|
Sign up to set email alerts
|

On chaotic dynamics in transcription factors and the associated effects in differential gene regulation

Abstract: The control of proteins by a transcription factor with periodically varying concentration exhibits intriguing dynamical behaviour. Even though it is accepted that transcription factors vary their dynamics in response to different situations, insight into how this affects downstream genes is lacking. Here, we investigate how oscillations and chaotic dynamics in the transcription factor NF-κB can affect downstream protein production. We describe how it is possible to control the effective dynamics of the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 42 publications
1
75
0
Order By: Relevance
“…Furthermore, it was recently confirmed the chaotic dynamics in the transcription factor NF-κB, a welldescribed transcriptional regulator in cancer networks, can affect downstream protein production (51). The nonlinear genetic oscillator NF-κB, when periodically driven by sufficiently large TNF (tumor necrosis factor) amplitudes, will exhibit deterministic chaos.…”
Section: Symmetry-breakingmentioning
confidence: 90%
“…Furthermore, it was recently confirmed the chaotic dynamics in the transcription factor NF-κB, a welldescribed transcriptional regulator in cancer networks, can affect downstream protein production (51). The nonlinear genetic oscillator NF-κB, when periodically driven by sufficiently large TNF (tumor necrosis factor) amplitudes, will exhibit deterministic chaos.…”
Section: Symmetry-breakingmentioning
confidence: 90%
“…Our results are in agreement with previous work and complement this work. For example, experimental evidence suggests that the affinity of essential regulators of gene expression, such as NF-κB and TBP, modulates gene expression noise (50,51). Moreover, a model based on the binding dynamics of Sox2 and Oct4, two important regulators of the pluripotency of stems cells, showed that long residence times reduce the sensitivity of gene expression to TF concentration, because TFs with long residence times are bound to DNA most of the time regardless of their concentration (26,31).…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be inferred that the endothelial response could be significant and probably chaotic, which determine transcription and gene regulation. 73 Chaos does not necessarily lead to dysfunctions, and at times and situations, it could be a natural method of selection to strengthen immune functions. Optical laser chaos signals which are high speed when studied are found to synchronize and it has many features.…”
Section: Chaos and Decodingmentioning
confidence: 99%